EVALUATION OF ANTI-TICK ACTIVITY OF Lawsonia inermis AND Nicotiana tabacum EXTRACTS AGAINST Haemaphysalis bispinosa (ACARI: IXODIDAE) - SAHINA, S.; ESAKKIAMMAL, B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Purpose: Ticks (Acari: Ixodidae) are the heamatophages arthropods and an important disease causing ectoparasites of animals and Human. Ticks are primarily controlled by the application of chemical acaricides, though tick populations control has not been achieved adequately. The objective of this present study is to appraise the acaricidal and repellent efficiency of Nicotiana tabacum and Lawsonia inermis extracts using different solvents against H. bispinosa. Methods: The leaves of N. tabacum as well as leaves and seeds of L. inermis were extracted by soxhlet apparatus with five solvents. The active compounds were analyzed by GC MS analysis. A stock solution of plant extracts was prepared in Dimethyl Sulpho Oxide and the subsequent concentrations of 5, 10.15, 20 and 25 mg/ml for acaricidal and 0.5, 1, 1.5,2, and 2.5 mg/ml for repellency bioassay were used as working concentration. Findings: Among the tested extracts, the methanolic and ethanolic extract of both the plants showed the highest activity against ticks. The percent larval tick mortality of N. tabacum and L. inermis varied from 46.9 % to 96.5%, at higher concentration of 25 mg/ml.The repellencies observed in extracts of N. tabacum leaf ranged from the lowest 0.5 mg/ml (31.9%) to the highest 2.5 mg/ml (99%) concentration. Conclusion: The results obtained from the study highlighted the ethanolic and methanolic extracts of Nicotiana tabacum and Lawsonia inermis plant products may be used as an alternative to synthetic anti-tick products.